DAKWAH DAN KOMUNIKASI KADER AL JAM’IYATUL WASHLIYAH DALAM PENGUATAN SYARIAT ISLAM DAN MODERASI BERAGAMA - Efendi, Sumardi; Herman, Herman (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
This research discusses the preaching and communication of Al Jam'iyyatul Washliyah cadres in strengthening Islamic law and religious moderation. Al Jam'iyyatul Washliyah is an Islamic organization that plays a crucial role in promoting a moderate understanding of Islam and building a society that adheres to Islamic law with wisdom and tolerance. This study employs a qualitative descriptive method to analyze the role of Al Jam'iyyatul Washliyah cadres in strengthening Islamic law and promoting religious moderation. Data were collected through in-depth interviews, participatory observation, and the study of documents related to the activities of Al Jam'iyyatul Washliyah cadres. The results of the research indicate that the preaching and communication of Al Jam'iyyatul Washliyah cadres play a significant role in disseminating a true understanding of Islamic law. They guide the community in practicing Islamic teachings in a contemporary context, steering clear of extremism, and promoting religious moderation. Cadres are also active in preaching and engaging in social, educational, and community empowerment activities to build a socially just and harmonious order in accordance with Islamic teachings.